Design and implementation of a system for transforming functional model into OO model - Yang, Yong; Tan, Hee Beng Kuan (Universiti Utara Malaysia, 2007)
This paper describes the design and implementation of prototype system, F200 for the enhanced data flow diagram, called data flow net (DF net) (Tan, Yang, & Bian), 2006). The prototype system transforms the software systems designed in DF net to OO design and implementation systemically, precisely and automatically. This has greatly enhanced the OO methodology by synthesizing functional decomposition, which is a well-developed concept in traditional structured methodology. The prototype system facilitates the software designer to construct the functional analysis models for some of the use-cases in their own systems in DF net. Thereafter, together with remaining use-cases using any existing OO software development methods, the whole systems can be implemented following current OO design and implementation. This is very useful in realizing use-cases, especially those with more complex functions.